1985
DOI: 10.1002/ar.1092130211
|View full text |Cite
|
Sign up to set email alerts
|

Bone lining cells and hematopoiesis: An electron microscopic study of canine bone marrow

Abstract: Hematopoietic bone marrow in the dog is enclosed by a nearly complete and rather complex layer of endosteum, consisting of a diverse group of cells collectively called bone lining cells (BLC). Cell types comprising BLC include osteoblasts and osteoclasts, and other cell types, among which are elongated, flat cells with a spindle-shaped nucleus, and small cytoplasmic vesicles. The composition and thickness of the layer of BLC varies along the perimeter of the marrow. The layer may be simple or stratified. Occas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 37 publications
0
19
0
1
Order By: Relevance
“…IL-3 is a cytokine produced by activated T cells, 43 which are not the predominant cells within the bone endosteum. 1 Furthermore, IL-3 promotes the commitment of HPCs to the myeloid lineage and acts as a survival factor for myeloid progenitors. 44,45 It is therefore likely that the inclusion of IL-3 reduces cell death at 2% O 2 by increasing survival of more committed (eg, CD34 dim ) cells that develop during culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-3 is a cytokine produced by activated T cells, 43 which are not the predominant cells within the bone endosteum. 1 Furthermore, IL-3 promotes the commitment of HPCs to the myeloid lineage and acts as a survival factor for myeloid progenitors. 44,45 It is therefore likely that the inclusion of IL-3 reduces cell death at 2% O 2 by increasing survival of more committed (eg, CD34 dim ) cells that develop during culture.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] A longitudinal cross section of the bone shows that the endosteum is the farthest site from the bone vasculature. Consistent with this observation, the endosteum has the lowest oxygen pressure, compared with other regions within the bone.…”
Section: Introductionmentioning
confidence: 99%
“…21 However, none of these methods was designed to isolate quiescent HSCs located within the osteoblastic niche, which is generally considered to house the most primitive HSCs. 6,[8][9][10][11]14,22,23 Since it is difficult to experimentally access viable cells within the osteoblastic niche, these HSCs have not been directly or indirectly isolated by taking advantage of any of the specific properties of the niche microenvironment, such as ROS activity. Recent studies showed exhaustion of HSCs in Atm-or FoxO-deficient mice.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Hematopoietic stem cells (HSCs) and the supporting cells of the stem-cell niche are predominantly located in a low-oxygen milieu of the bone marrow, which allows long-term protection from ROS-related oxidative stress. 4,6,7 In the osteoblastic niche, the lowest end of an oxygen gradient within the bone marrow, 6,[8][9][10] HSCs remain quiescent and in contact with osteoblasts, 11 whereas in the relatively more oxygenic vascular niche, due to the proximity to blood circulation, stem cells actively proliferate and differentiate, [12][13][14][15] which might increase the intracellular ROS level. 1 In the osteoblastic niche, the calcium-sensing receptor (CaR) plays a critical role in localizing HSCs to the endosteal surface, although it does not affect HSC homing, 16 and osteoblast-derived factors have been suggested to improve survival of umbilical cord-derived HSCs under hypoxic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Even before the unambiguous demonstration of marrow-bone integration at the anatomical level as shown here, it had been hypothesised that cells of the endo-osteal layer, such as bone-lining cells, were continuous with the stromal system of the bone marrow and that they may have been involved with haematopoietic functions (Deldar et al 1985). It is also known that in the regeneration of marrow following mechanical damage or ectopic transplantation (Tavassoli and Friedenstein 1983), the marrow haematopoietic volume is influenced by not only the degree of sinusoidal dilatation, and the degree of fatty change in reticular adventitial cells, but also by the extent and thickness of trabeculae.…”
Section: Discussionmentioning
confidence: 87%